Dabigatran‐induced esophagitis: The prevalence and endoscopic characteristics. Issue 3 (26th February 2016) - Toya, Yosuke; Nakamura, Shotaro; Tomita, Kazumitsu; Matsuda, Nozomi; Abe, Keinosuke; Abiko, Yukito; Orikasa, Shunsuke; Akasaka, Risaburo; Chiba, Toshimi; Uesugi, Noriyuki; Sugai, Tamotsu; Matsumoto, Takayuki
Abstract: Background and Aim: There have been some descriptions of dabigatran‐induced esophagitis in the literature. The aim of this study was to examine the prevalence and endoscopic characteristics of the disease. Methods: We reviewed the endoscopic database and medical records of 91 patients with dabigatran internal use who underwent upper gastrointestinal endoscopy. The frequency of dabigatran‐induced esophagitis and its endoscopic findings were retrospectively analyzed. In addition, the clinical characteristics were compared between patients with dabigatran‐induced esophagitis and those without the disease. Results: Dabigatran‐induced esophagitis was found in 19 of 91 (20.9%) patients. Of the 19 patients with the esophagitis, 18 (94.7%) showed longitudinally sloughing epithelial casts in the mid and/or lower esophagus, which may be characteristic endoscopic findings of this disease. Symptomatic patients were more frequent in patients with dabigatran‐induced esophagitis (68.4%) than those without (37.5%, P  = 0.02). Other factors including age, gender, coexistence of hiatal hernia, gastroesophageal reflux disease, or concomitant other medications did not differ between the two groups. Conclusions: Dabigatran causes the esophageal mucosal injury in approximately 20% of patients. Longitudinally sloughing casts in the distal esophagus are characteristic of dabigatran‐induced esophagitis.